Challenging the ‘invariance’ thesis: procedural justice policing and the moderating influence of trust on citizens’ obligation to obey police - Murphy, Kristina (Journal of experimental criminology, 2017)
This paper examines the effects of a procedural justice policing intervention on citizens’ feelings of obligation to obey police. It examines whether the efficacy of procedural justice on citizens’ obligation to obey police may be contingent on citizens’ level of trust in police during a police-citizen encounter.